Neanderthal brain and cognition reconsidered - P. Thomas Schoenemann; Ralph L. Holloway; Jia-Hong Gao; Guoyuan Yang (Proceedings of the National Academy of Sciences, 2026)
Neanderthal endocrania are different in shape, though slightly larger in size than modern humans on average. These shape differences have long been used to suggest Neanderthals differed cognitively from modern humans, e.g., by having inferior linguistic/symbolic ability, poorer executive function, and/or smaller episodic and working memory capacity. However, whether the morphological differences in their brains inferred from their endocrania indicate truly meaningful cognitive/behavioral differences—with real evolutionary implications—is not clear. Recent work using deformation mapping techniques suggested there had been significant brain differences between Neanderthal and the anatomically modern Homo sapiens (am Hs ) that were contemporary with them. However the inferred differences were not put into the context of modern human populational variation in brain anatomy, which is known to be substantial. We estimate MRI brain region volumes in two modern population samples (US and Chinese) using deformation mapping and find similar sized differences to those reported for Neanderthal vs. am Hs , with 9 of 13 brain regions showing larger absolute differences for US vs. Chinese samples as compared to reported Neanderthal vs. am Hs differences. To the extent that brain anatomy differences indicate cognitive differences, this suggests that cognitive differences between Neanderthals and am Hs would have comfortably fit within the range found among modern human populations—which are generally not considered evolutionarily significant. In fact, the endocranial differences between Neanderthal and their contemporaries predict cognitive difference effect sizes of only 0.14 SDs or less. This undermines the suggestion that Neanderthal replacement occurred because of cognitive limitations.